FACTORS AFFECTING THE MANAGEMENT OF THINKING SYSTEMS: COMPETENCE, EDUCATION AND MOTIVATION (Literature Review) - Firmanto, Rian Anugrah; Ali, Hapzi; Rosadi, Kemas Imron (Teunuleh Publisher, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and influence of relationships or influences between variables. This article reviews the factors that affect System Thinking Management, namely: Competence, Education, and Motivation, a literature study of Islamic Education Management. The purpose of writing this article is to build a hypothesis of influence between variables to be used in future research. The results of this literature review article are: 1) Competence affects System Thinking Management; 2) Education affects the Management thinking system; and 3) Motivation affects System Thinking Management.